The Influence of Islamic Teachings on the Leadership of the 4th Sultan of Demak (Pengaruh Ajaran Agama Islam dalam Kepemimpinan Sultan Demak Ke-IV) - Majrizka, Muhammad Daffa; falaq, Yusuf (Institut Agama Islam Negeri (IAIN) Kendari, 2024)
This study analyzes the reign of Sunan Prawoto during the Demak Sultanate from 1546 to 1549 AD, employing the historical research method and the cyclical theory framework proposed in Ibn Khaldun's Muqaddimah. The findings reveal that Sunan Prawoto, the fourth Sultan of the Demak Sultanate, ascended the throne amid political instability and faced internal and external threats. To stabilize the state, he moved the capital to Bukit Prawoto and aimed to unite Java under his rule, envisioning a leadership akin to the second Sultan of Turkey. This study concludes that Sunan Prawoto's efforts were significant in shaping the political landscape of the Demak Sultanate.Keywords: History of Sunan Prawoto; Teachings of Sunan Prawoto; Fourth Sultan of Demak; Government of Sunan Prawoto